Are boards of directors in Malaysia ethnically diversified? - Ahmad Zaluki, Nurwati Ashikkin (2008)
This paper examines the ethnic profile of board members in 235 newly listed Malaysian companies at the time of public offerings during the period 1999 to 2006. Using Blau’s (1977) index of heterogeneity, we find evidence of the existence of ethnic diversity among board members of these companies. Further analysis reveals that the boardrooms of our sample are dominated by the Chinese ethnic group, followed by Malays, Indians and others. Our results indirectly suggest that harmonious relations between board members from different racial and ethnic backgrounds exist in Malaysia.